Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus - Elvebakk, Arve; Bjerke, Jarle W. (PhytoKeys, 2024)
Papaveraceae tribus Papavereae includes an American and a mainly Eurasian group of genera. The latter is proposed here to include eight genera. Amongst these, the recently described genus Oreomecon is phylogenetically a sister group to Meconopsis, a genus from Himalaya and central China, which is reviewed here as including 95 species and 21 subspecies. By contrast, Oreomecon has a circumpolar northern alpine and Arctic distribution, including incompletely understood taxa, many threatened by climatic warming. Based on a review of literature and phylogenies, it is proposed here that Oreomecon includes 68 species and 29 subspecies. Oreomecon aurantiaca, O. cornwallisensis, O. keelei, O. ochotensis and O. uschakovii, 29 subspecies and four varieties are placed in Oreomecon here, 29 of these as recombinations, the remaining ones as nomenclatural novelties. A total of 21 existing Oreomecon names are placed into synonymy. The taxonomically challenging O. alpina group from Central Europe is treated as comprising three species, with the remaining entities positioned at the subspecies level pending further studies. The much-studied Nordic species O. radicata is treated with eight subspecies here, based on morphometric studies, whereas four accepted entities are provisionally recombined at the variety level. The name Papaver tenellum and the basionyms of Oreomecon alborosea, O. alpina subsp. corona-sancti-stephani, O. alpina subsp. degenii, O. anomala, O. lapeyrouseana subsp. endressii, O. lapponica subsp. laestadiana and O. nivalis are lectotypified here. Two replacement names, Oreomecon alpina subsp. markgrafiana and O. radicata subsp. knabeniana, are introduced. Papaver, as currently understood, is recircumscribed here to represent four genera. The isolated section Horrida, from southern Africa, is raised to genus level with the new name Afropapaver and its only species is recombined as Afropapaver aculeatum. Papaver sect. Californica from California and adjacent Mexico is treated as the genus Stylomecon. The name has ...